(untitled) (MAUSAM, 1956)
A study of the Manipur-Burma earthquake of 22 March 1954, which was felt over a large part of Eastern India and neighbourhood, has been made using data from allover the world The epicentre has been found as 24°,38N, Long, 95°,15 E and the origin time as 23 h 42 m 12.5 s GMT, The depth of focus using four methods has been calculated as 180:J: 10 km, An isoseismal map has been drawn from macroseismic information collected from India, Burma, East Pakistan and Lhasa. From the direction of first motion, as recorded at different Indian and extra-Indian observatories, the direction of faulting has been determined and discussed, Records of aocelerographs at Shillong and Chatra show that the numbers 6 and 4 of the Modified Mercalli scale of intensity at these places correspond to the recorded maximum (horizontal) accelerations of 5 cm sec-2 and 2 cm sec-2 respectively. These correspond to the minimum acceleration of the ranges as determined by United States Coast and Geodetic Survey from accelerograph data collected during 1930-41.